CARACTERIZACIÓN ZOOTÉCNICA DEL GANADO DE LIDIA DE LA EMPRESA HACIENDA CERRO NUEVO S.A.C. EN PAIJÁN-LA LIBERTAD - De la Cruz Montenegro, Araceli Lucia (2017)
The present study: Zootechnical Characterization of Livestock of Lidia in the Hacienda Cerro Nuevo S.A.C, Paiján, was carried out with the purpose of characterizing the animals of the El Olivar, La Viña, Paiján and Cerro Viejo cattle farms; using a total of 245 animals, through a retrospective descriptive investigation of data recorded by the year 2013. The most evaluated parameters are referred to heritability, caste, age at encaste and fighting, bravura, type of antler, blanket and sex of animals; with a significant positive correlation between bravery and other quantitative parameters. The El Olivar and Cerro Viejo herds have an average heritability of 0.21; El Olivar presents a high performance encaste; La Viña and Paiján, a medium performance encaste; The referential caste of most animals in the herds in study: El Olivar, La Viña, Paiján and Cerro Viejo, is the Santa Coloma cattle ranch; In front of the referential caste Juan Pedro Domecq, of the minority of animals: El Olivar, La Viña, Paiján and Cerro Viejo; The average age of the temptation is 2.34 years, and, to the fight, 3.29 years; El Olivar, Cerro Viejo and La Viña show significant bravery; Paiján, a less significant bravery; The mulatto blanket, the black color, both in El Olivar and La Viña, and blue in Paiján, are the most frequent blanket color in the herds under study; Cornelantero and cornelón are the most common types of antlers; The average percentage of females is 41.42%, compared to males, of 58.58%; Being the livestock El Olivar who shows averages of 49.43% in females and 50.57% in males. It is concluded that cattle from the Hacienda Cerro Nuevo S.AC., Paiján, is characterized by being a vaccine population that has lost its original phenotype manifested in racial characters mixed with local cattle.